Clinical and immunohistochemical performance of lyophilized platelet‐rich fibrin (Ly‐PRF) on tissue regeneration. (13th February 2017) - Zhang, Jianming; Qi, Xingying; Luo, Xiaoding; Li, Dan; Wang, Haorong; Li, Ting
Abstract: Background: Platelet‐rich fibrin (PRF) has been widely used in oral implantology and other fields, but benefits of the fresh PRF (FPRF (fresh platelet‐rich fibrin)) were consequently limited because of its short‐term application. Thus, a protocol for the combination of PRF and lyophilization comes up in the present study to address the issue of PRF storage and delayed clinical application, which has little been reported in this field at home and abroad by now. Purpose: The aim of the present study was to evaluate the applicability of lyophilized platelet‐rich fibrin (Ly‐PRF) used as the scaffold material for craniofacial tissue regeneration and to compare its biochemical properties with commonly used fresh PRF. Materials and Methods: Two volunteers with both genders were selected as the source of PRF and Ly‐PRF samples. Macro‐ and micro‐scopic appearance evaluation as well as immunohistochemical comparison were performed on PRF samples before and after freeze‐drying at −196°C. The second experimental phase was to observe clinical performance when fresh and lyophilized PRF were applied in guided bone regeneration (GBR) operations in 39 patients losing teeth in the anterior maxillary region who required an oral implantation followed by labial bone grafting. Results: The conventional histological and transmission electron microscopy images showed the microstructure of Ly‐PRF, which resembled a mesh containing apparently irregularly shaped platelets with less alpha‐granule than fresh PRF in micro and a translucent membrane with less elasticity than fresh PRF in macro. Simultaneous immunohistological staining results showed positive expression of PDGF‐BB, IL‐1, IL‐4, TNF, TGF‐β1 in both fresh and lyophilized PRF, while the expression of PDGF‐BB, IL‐1, TNF, TGF‐β1 has no statistical difference between them ( P > .05) but that of IL‐4 in Ly‐PRF is statistically higher than in fresh PRF ( P < .05). When applied in GBR operations, there were no significant differences between Ly‐PRF and FPRF in factors of histological and clinical evaluations (i.e., color, swelling, bleeding of the mucosa, pain leveland, and remodeling of hard tissue) performed 3 days, 7 days, and 4 months after the surgery ( P > .05). Conclusions: This study strongly supports that lyophilization at −196°C does not largely influence the expression of bioactive factors, the microstructure of fibrinogen or the clinical effects of PRF.